PEMBUATAN DESAIN KARAKTER ANIMASI 2D â€œTERJEBAK HOAKSâ€ DALAM BENTUK VEKTOR - Umi Kalsum Nasution; Muchamad Fajri Amirul Nasrullah; Sandi Prasetyaningsih; Anis Rahmi (Politeknik Negeri Batam, 2023)
Traditional 2D animation is time-consuming and costly, but technological developments have brought innovations in 2D animation creation through digitization. Vector-based 2D animation uses computer software and utilizes vector-based images to produce smooth animation. The advantages of vector-based 2D animation are the flexibility in character changes and editing, as well as the ability to reuse vector images that have already been created. This saves animation production time and costs and speeds up the production process through rigging and tweening techniques. The character design production process of the 2D animation